2021
DOI: 10.1002/jmor.21342
|View full text |Cite
|
Sign up to set email alerts
|

Sensilla of the antenna and proboscis of Athetis lepigone (Möschler) (Lepidoptera: Noctuidae)

Abstract: Sensory structures on the antennae and mouthparts of insects are associated with various activities, such as host location, feeding, attracting a mate, and identifying a suitable oviposition site. Athetis lepigone (Möschler) is an important polyphagous Eurasian pest with more than 30 species of host plants. The larvae target bud leaves, prop roots, and tender stems of many agricultural crops, but the feeding habits of the adults remain poorly known. Aiming to understand the feeding behavior of the species, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
(105 reference statements)
3
6
0
Order By: Relevance
“…The noctuid moths are mostly flower-visiting pollinators, and use the proboscis tip to pollinate [64][65][66]. These two species, S. trifolii and P. scutosa, are most likely to be flowervisiting noctuids, and characterized by elongated sensilla styloconica and modified dorsal legulae on the proboscis, as reported in previous studies [15,19,20,67,68]. The conclusion is also reinforced by the presence of floral pollen at the proboscis tip of P. scutosa (Figure 2).…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…The noctuid moths are mostly flower-visiting pollinators, and use the proboscis tip to pollinate [64][65][66]. These two species, S. trifolii and P. scutosa, are most likely to be flowervisiting noctuids, and characterized by elongated sensilla styloconica and modified dorsal legulae on the proboscis, as reported in previous studies [15,19,20,67,68]. The conclusion is also reinforced by the presence of floral pollen at the proboscis tip of P. scutosa (Figure 2).…”
Section: Discussionmentioning
confidence: 71%
“…Compared with S. trifolii, P. scutosa possess a long proboscis with a narrow tip, which might suggest that P. scutosa could better stretch into a long and slender flower tube than S. trifolii. In the potential flower visiting noctuids, Zone 3 is present on the proboscis tip of S. trifolii and P. scutosa, and absent on the proboscis tip of M. separata and A. lepigone [12,20,72]. The presence of Zone 3 might have adaptive value in facilitating the proboscis to enter narrow floral corollas, as described in Lehnert et al [22].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Furthermore, as shown in the RT-qPCR, in addition to be expressed in the tarsi, most of the annotated SfruGRs were also highly expressed in the proboscises. It has long been reported that many chemosensilla are distributed on the mouthpart and that the mouthpart functions in chemosensation in moths ( Krenn, 2010 ; Liu et al, 2014 ; Hu et al, 2021 ). Therefore, systematic analysis of GRs in other taste organs such as proboscis are still needed in the future.…”
Section: Discussionmentioning
confidence: 99%